A mente biológica: Filosofia, biologia evolutiva e neurociência no naturalismo biológico de John Searle - Lima Filho, Maxwell Morais de (2018)
In the present work we explore the philosophical, evolutionary and neuroscience parts that pervade the biological naturalism, the theory proposed by the philosopher John Rogers Searle as a solution to the mind-body problem. On the first chapter we draw a historical overview of the main concepts in this theoretical project. In the second we explain how critics from Searle to the main currents on Philosophy of the Mind, such as: the dualism of substance, the dualism of property, analytic behaviorism, the theory of mind-brain identity, functionalism and eliminativism. In the third and fourth chapters, we employ the distinction outlined by Ernst Mayr between Evolutionary Biology and Functional Biology to support that Searle is committed with two biases when asserts that mental phenomena are biological phenomena, namely: the phylogenetic and ontogenetic approaches of biological naturalism. Finally, in the last Chapter we argue that the conception of mental causation espoused by the american philosopher puts uneasy alternatives to the epiphenomenalism and overdetermination, although, as we shall argue, such a dilemma is not inevitable.